THE GOVERNMENT OF BANDUNG CITY’S EFFORTS IN UTILIZING FOREIGN SOURCES: Case Study in Sister City Cooperation - Alam, Gilang Nur; Dermawan, Windy; Affandi, RMT (CosmoGov: Jurnal Ilmu Pemerintahan, 2020)
This article aims to analyze the efforts of the Government of Bandung City in fulfilling its sub-national interests by utilizing sister city cooperation as a form of foreign sources. The Bandung City Government endeavors to conduct sister city cooperation, which is one of the activities resulting from the paradiplomacy, to meet its needs without having to depend on the central government. To achieve the objective, this research explores and analyzes data using qualitative methods by collecting primary data through interviews with some relevant informants and secondary data through documentation and literature studies. This research finds out that Bandung City Government’s sister city efforts are carried out in economic, social, and cultural cooperation with local governments abroad. However, sister city cooperation has a limitation in fulfilling the sub-national interests of Bandung City due to its government-to-government nature of the relationship. Meanwhile, there are other alternatives in utilizing other foreign sources aside from sister city cooperation, for example, the optimization of individual and private sectors’ paradigmatic activities. Hence, Bandung City Government needs to re-develop wider regional foreign relations by involving other actors besides sub-national actors abroad. gb777